Employee Performance at the North Bekasi Pratama Tax Service Office is Influenced by Leadership Style and Communication Through Job Satisfaction as an Intervening Variable. - Wahyu Ary Wibowo; Silitonga, Eddy Sanusi P; Guswandi (Madani Connection, 2025)
This study aims to: 1) find out the description of leadership style, communication, job satisfaction and employee performance, 2) find out the influence of leadership style on employee performance, 3) know the influence of communication on employee performance, 4) know the influence of leadership style on employee job satisfaction, 5) know the influence of communication on employee job satisfaction, 6) find out the influence of job satisfaction on employee performance, 7) to know the influence of leadership style on employee performance through job satisfaction as an intervening variable, 8) to know the influence of communication on employee performance through job satisfaction as an intervening variable.The research was conducted with a sample of 117 respondents. The sampling technique uses the saturated sample technique. The data analysis method uses descriptive analysis, regression analysis, path analysis, and Sobel test. The path analysis model was tested with the SPSS Version 27 program.The results of the regression equation show that 1) there is a positive and significant influence between leadership style on employee performance, 2) there is a positive and significant influence between communication on employee performance, 3) there is a positive and significant influence between leadership style on job satisfaction, 4) there is a positive and significant influence between communication on job satisfaction 5) there is a positive and significant influence between job satisfaction on employee performance, 6) there is no positive and significant influence between leadership style and employee performance, 7) there is no positive and significant influence between communication on employee performance.The results of the mediation variable influence test showed that the direct influence was greater than the indirect influence, this mediation influence was expressed as partial mediation. The real influence is the direct influence of leadership style on employee performance and communication on employee performance. change management to the company's performance. The results of the Sobel test showed that the t-statistical value was significantly smaller than the t-table, it was concluded that job satisfaction did not mediate the relationship between leadership style and employee performance and the relationship between communication and employee performance